KOMODIFIKASI NILAI KEARIFAN LOKAL PURA ULUWATU SEBAGAI OBYEK WISATA RELIGI DI BALI (Jurnal PATRA, 2024)
Bali is an island of a thousand temples that has undergone many transformations due to the development of the tourism sector. The natural beauty and elegance as well as the unique culture that it has attracts tourists to come to visit. Uluwatu Temple, located in Pecatu Village, South Kuta District, Badung Regency, is one of the rich cultural heritages whose sustainability is considered important for the surrounding community in particular and the people of Bali Province in general. As one of the Sad Kahyangan temples located in the southwest direction of Bali Island, Uluwatu Temple is rich in intangible and tangible heritage values. This is then utilized and transformed into a commodity for Uluwatu Temple and the community in the surrounding area. The problems that will be raised in this research are: (1) The process of commodification of local wisdom values ​​at Uluwatu Temple in terms of Commodification Theory by Vincent Mosco and (2) Strategy for developing Uluwatu Temple as a cultural heritage as well as a religious tourism object The use of descriptive qualitative methods with a phenomenological approach was considered the most appropriate for completing this research. The author hopes that the academic community, architectural observers, cultural observers and the general public can understand the commodification of local wisdom values ​​at Uluwatu Temple and know the strategy for developing Uluwatu Temple as a cultural heritage as well as a religious tourism object so that it is sustainable for the next generation. Key words: Commodification, Local Wisdom, Uluwatu Temple, Religious Tourism Objects Bali merupakan pulau seribu pura yang mengalami transformasi berkali-kali akibat berkembangnya sektor pariwisata. Keindahan dan keelokan alam serta keunikan budaya yang dimiliki menjadi minat para wisatawan untuk datang berkunjung. Pura Uluwatu berlokasi di Desa Pecatu, Kecamatan Kuta Selatan, Kabupaten Badung adalah salah satu kekayaan warisan budaya yang keberlanjutannya dinilai penting bagi masyarakat sekitar pada khususnya dan masyarakat Provinsi Bali pada umumnya. Sebagai salah satu Pura Sad Kahyangan yang bertempat pada arah Barat Daya Pulau Bali, Pura Uluwatu kaya akan nilai intangible dan tangible heritage. Hal tersebut yang kemudian dimanfaatkan dan ditransformasikan menjadi komoditas bagi Pura Uluwatu dan masyarakat di lingkungan sekitar. Permasalahan yang akan diangkat pada penelitian ini adalah : (1) Proses komodifikasi nilai kearifan lokal pada Pura Uluwatu ditinjau dari Teori Komodifikasi oleh Vincent Mosco dan (2) Strategi pengembangan Pura Uluwatu sebagai warisan budaya sekaligus obyek wisata religi. Penggunaan metode kualitatif deskriptif dengan pendekatan fenomenologi dinilai paling sesuai untuk menyelesaikan penelitian ini. Penulis berharap agar civitas akademika, pengamat arsitektur, pengamat budaya dan masyarakat umum dapat memahami komodifikasi nilai kearifan lokal pada Pura Uluwatu dan mengetahui strategi pengembangan Pura Uluwatu sebagai warisan budaya sekaligus obyek wisata religi agar berkelanjutan untuk generasi berikutnya. Kata Kunci: Komodifikasi, Kearifan Lokal, Pura Uluwatu, Obyek Wisata Religi